Training for success: Do simulated aerial landings replicate successful aerial landings performed in the ocean? - Forsyth, J. R.; Riddiford-Harland, D. L.; Whitting, J. W.; Sheppard, J. M.; Steele, J. R. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Purpose: Physical preparation of competitive surfers includes substantial dry-land training. It is currently unknown, however, how closely these exercises replicate surfing manoeuvres performed in the ocean. This study compared the technique features displayed by surfers when landing simulated aerial manoeuvres on land to critical features previously established as necessary for surfers to successfully land aerials in the ocean during competition. Methods: Fourteen competitive surfers (age 20.6±5.7 years, height 178.1±9.50 cm, mass 70.6±10.8 kg) were recruited to perform two variations of a simulated aerial task, a Frontside Air (FA) and Frontside Air Reverse (FAR). Joint ranges of motion (ROM), centre of pressure and apparent gaze data were collected during the landing event. Paired t-tests or Wilcoxon Signed Rank tests were used to identify any significant differences in the outcome variables between the two aerial tasks. Results: Participants displayed 100% and 60% of the critical features associated with successfully landing a FA and FAR, respectively. In both the simulated FA and FAR, participants landed in 1.0-3.7° of dorsiflexion, moving through significantly less ankle joint ROM in the lead limb during the FAR (p < 0.01). Participants also displayed significantly less knee and hip ROM (p = 0.002-0.048) while landing the FAR compared to the FA. Conclusion: The simulated FA and FAR tasks are appropriate training tools for surfers to replicate most of the critical features that a surfer should display to successfully land aerial manoeuvres in the ocean. These tasks therefore enable surfers to practice these complex movements in a controlled environment.